CURRENT STATE OF CT/MRI SPINAL CANAL STENOSIS DIAGNOSIS AT THE LUMBOSACRAL LEVEL (REVIEW) - A. S. Sementsov; V. V. Ponomarenko (Сучасні медичні технології, 2020)
Issues of epidemiology, classification and radiological signs of the spinal stenosis in this review are present. Modern European criteria for spinal stenosis and radicular openings can improve the diagnosis of the condition of the spinal cord and roots; clarify the criteria for indications for surgical treatment.